Mutational analysis of phenolic acid decarboxylase from Enterobacter sp. Px6-4. towards enhancement of binding affinity: A computational approach. (October 2018) - Kumar, Pravin; Kumari, Priya; Sachan, Shashwati Ghosh; Poddar, Raju
Graphical abstract: Highlights: Ferulic Acid Decarboxylase (FADase) catalyzes the conversion of ferulic acid to 4-vinylguaiacol. Sequential site directed mutations were introduced on active site of FADase and validated with DCCM, PCA and MD simulation. Docking studies were performed between ferulic acid and different mutants of FADase. Best mutant-ligand complex was validated through stable energy optimization. New mutants were reported with higher affinity towards and more hydrogen bonds formation. Abstract: Microbial Ferulic Acid Decarboxylase (FADase) catalyses the conversion of ferulic acid to 4-hydroxy-3-methoxystyrene (4-vinylguaiacol) via non-oxidative decarboxylation. In this article, we present a computational, three-dimensional structural and functional analysis of FADase from Enterobacter sp. P × 6-4 (3NX1) which can be used to generate enhanced bindings of substrates. The enzymatic catalytic site and binding sites have been critically evaluated. Sequential site directed mutations on enzyme have also been introduced for formation of a greater number of hydrogen bonds. Four mutants were generated based on our hypothesis. Active sites of mutated FADases have been analyzed with dynamic cross-correlation maps and principle components analysis. All structures were validated and optimized through energy minimization. Docking studies were also carried out between ferulic acid and different mutated enzymes. The protein (wild and mutants) complexes were further validated with molecular simulation. Mutant3 was found to have better affinity towards ferulic acid. Mutant3 also forms a higher number of hydrogen bonds with the substrate to facilitate greater interaction. This current work will help industry to create new and novel mutants to produce vanillin.